Pengembangan E-Lkpd Pertumbuhan dan Perkembangan Tumbuhan Berbasis Guided Discovery untuk Melatihkan Keterampilan Proses Sains Terintegrasi - Ira Hasanah; Wisanti Wisanti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Abstract Integrated science process skills are one of the demands of the 21st century. The guided discovery model can be applied in learning to train integrated science process skills. The research aims to produce an E-LKPD based on guided discovery for plant growth and development to train integrated science process skills that are theoretically and empirically feasible. This research is development research using the 4D mode, which consists of defining, designing, developing, and disseminating. This research only reached the development stage. Theoretical feasibility based on the validation results includes presentation, content, and language aspects. Empirical feasibility is obtained from the integrated science process skills test-score and students’ responses. E-LKPD is categorized as theoretically feasible if it scores ≥ 2.51. E-LKPD was classified as empirically feasible if the percentage of students on the achievement of integrated science process skills indicators ≥ 76% and strong criteria student responses ≥ 61%. The results of theoretical feasibility in the validation test obtained a score of 3.86 (very valid). The empirical feasibility of E-LKPD is shown by the test results showing the achievement of integrated science process skills indicators obtaining good to very good criteria, namely formulating problems, formulating hypotheses, identifying variables, carrying out experiments, presenting data, analyzing data, formulating conclusions successively by 96.7%; 91.7%; 86.6%; 91%; 96%; 78.3%; 91.7%, and the results of students' responses 97.25% (very strong). E-LKPD is declared theoretically and empirically feasible to use in learning. Key words: E-LKPD, guided discovery, growth, development, integrated process skills.